2022
DOI: 10.1111/jipb.13371
|View full text |Cite
|
Sign up to set email alerts
|

Egg cell‐secreted aspartic proteases ECS1/2 promote gamete attachment to prioritize the fertilization of egg cells over central cells in Arabidopsis

Abstract: Double fertilization is an innovative phenomenon in angiosperms, in which one sperm cell first fuses with the egg cell to produce the embryo, and then the other sperm fuses with the central cell to produce the endosperm. However, the molecular mechanism of the preferential fertilization of egg cells is poorly understood. In this study, we report that two egg cell‐secreted aspartic proteases, ECS1 and ECS2, play an important role in promoting preferential fertilization of egg cells in Arabidopsis. We show that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 46 publications
(60 reference statements)
2
17
0
Order By: Relevance
“…As a consequence, partially semigamous zygotes and haploid offspring were generated (Zhang et al, 2023). More recently, Jiang et al (2022) confirmed the critical role of ECS1/2 in plant fertility and discussed that the endopeptidases are also involved in gamete interaction. These authors concluded, based on their data, that ECS1 and ECS2 were secreted from the egg cell already before fertilization and function to promote sperm cell attachment to the egg cell.…”
Section: Figurementioning
confidence: 87%
See 4 more Smart Citations
“…As a consequence, partially semigamous zygotes and haploid offspring were generated (Zhang et al, 2023). More recently, Jiang et al (2022) confirmed the critical role of ECS1/2 in plant fertility and discussed that the endopeptidases are also involved in gamete interaction. These authors concluded, based on their data, that ECS1 and ECS2 were secreted from the egg cell already before fertilization and function to promote sperm cell attachment to the egg cell.…”
Section: Figurementioning
confidence: 87%
“…Notably, Jiang et al (2022) observed that sperm cells remained outside of the unfertilized egg cells at 30 hap, and unfused sperm cells were found detachable at 24 hap from egg cells of the ecs1‐1 ecs2‐1 mutant. Therefore, the authors concluded that ECS1 and ECS2 significantly contribute to egg cell–sperm cell attachment.…”
Section: Figurementioning
confidence: 98%
See 3 more Smart Citations